The efficacy of different extrapleural fixations in upper-posterior thoracoplasty in fibrous cavernous pulmonary tuberculosis patients - S. A. Belov; A. A. Grigoryuk (Туберкулез и болезни лёгких)
The objective of the study: to compare the efficacy of different modifications of thoracoplasty in patients with apical fibrous cavernous pulmonary tuberculosis.Subjects and methods. The article describes the analysis of the results of thoracoplasty in 65 fibrous cavernous pulmonary tuberculosis patients performed from 2016 to 2019. Three types of thoracoplasty were used: thoracoplasty with polypropylene mesh, osteoplastic thoracoplasty, and traditional thoracoplasty. The results were assessed by the severity of intraoperative trauma, development of bronchopulmonary complications, lack of compression, and healing of cavities.Results. No significant difference in the degree of intraoperative injury was found when comparing three types of thoracoplasty (p > 0.05). Clinical and X-ray examinations of patients in 3 weeks after surgery revealed that in thoracoplasty with a polypropylene mesh, the frequency of bronchopulmonary complications and lack of compression was lower than in other types of thoracoplasty (p < 0.05). Using the patient's own tissues for extrapleural fixation, especially with large cavities, results in a significant decrease in the thoracoplasty efficacy.